Just-in-time manufacturing and purchasing practices and business performance: an exploratory study / Che Ruhana Isa and Tay Yew Keong - Isa, Che Ruhana (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2008)
In today's challenging and turbulent competitive markets, companies need to constantly review their strategies in order to survive and sustain their market positions. One of the strategies frequently adopted by companies to improve manufacturing performance is Just-in-time purchasing and manufacturing practices. Use of JIT enables them to be more efficient, effective and more responsive to customer needs as JIT is based on the philosophy of demand pull and lean manufacturing. This study investigates the relationship between the level of just-in-time (JIT) purchasing and manufacturing practices and performance. It employed a self-administered questionnaire survey to collect data from Malaysian manufacturing companies.